Influence of preparation methods on the antioxidant activities of Saba Banana (Musa acuminata Colla x Musa balbisiana Colla (ABB Group)) leaves used as food contact material - Delos Reyes, Richelle Jeanine M.; Villarino, Casiana Blanca J.
The study aimed to evaluate the influence of preparation methods on the antioxidant activities of saba banana (Musa acuminata Colla x Musa balbisiana Colla (ABB Group)) leaves (SBL) used as food contact material (FCM). Specifically, the study determined the total phenolic content (TPC), and total antioxidant activity through percent scavenging activity (%SA) of SBL subjected to different preparation methods, and established the preparation method that has the most effective retention of its inherent antioxidant activity using TPC (mg GAE/mL), %SA, and IC50 (Inhibition Concentration of Sample required to scavenge 50% of DPPH radicals) value. Preparation methods employed for SBL had a significant (p<0.05) effect on its TPC and % SA. Amongst the preparation methods, singeing had the greatest potential in retaining the antioxidant activity of SBL. Singed SBL had 0.009937 ± 0.002554 mg GAE/mL TPC, 39.08 ± 16.40 – 51.71 ± 5.00 %SA, and an IC50 value of 0.0457 ± 0.0800 mg/mL, indicating a high antioxidant activity. Overall, the results of the study would be beneficial for food vendors in preparing saba banana leaves that may have the maximum antioxidant activity which may aid in the extension of the food’s shelf life.